Could some give a little help.
$\displaystyle \frac{1}{\left(s^2+0.76s+1\right)\left(s^2+1.84s+1 \right)}=\frac{\text{A1s}+\text{A2}}{s^2+0.76s+1}+ \frac{\text{B1s}+\text{B2}}{s^2+1.84s+1}$
In order that two polynomials be equal for all values of the variable coefficients of the same powers must be equal.
Here you have
$\displaystyle 0 s^3+ 0s^2+ 0s+ 1$$\displaystyle =s^2 (1.84 A+B+0.76 C+D)+s (A+1.84 B+C+0.76 D)+s^3 (A+C)+B+D$
so you must have 1.84A+ B+ 0.76C+ D= 0, A+1.84B+ C+ 0.76D= 0, A+ C= 0, and B+ D= 1. That gives you four equations to solve for A, B, C, and D.